ANALISIS PENILAIAN ORGANOLEPTIK DAN NILAI GIZI COOKIES FORMULASI TEPUNG Wikau Maombo - Utami, Andi Pratiwi (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
Cassava is widely used as local food in many areas of Indonesia, including in Buton, Southeast Sulawesi. A local modified cassava flour in Buton, called wikau maombo, has been produced by Butonese since a long time ago. This modified product has been claimed to have a unique characteristic, and made through a fermentation treatment. Based on the previous researches, the 3-days fermentation has been assessed to have a better sensory characteristic. This study was aimed to evaluate the sensory and nutritional values of the cookies made from this wikau maombo flour. The study employed Completely Randomized Design with factorial. The two factors were: W1 (wikau maombo made from sweet cassava) and W2 (wikau maombo made from bitter cassava). The second factor was the proportion of wikau maombo and wheat flour, namely T0 (100% wikau maombo), T1 (90% wikau maombo – 10% wheat), T2 (85% wikau maombo – 15% wheat), T3 (75% wikau maombo – 25% wheat) dan T4 (100% wheat). The best sensory assessment was found in the formulatin of 85% wikau maombo – 15% wheat (W2T2). The sensory values were: aroma of 3.65 out of 5.00 (quite like), and taste of 3.67 out of 5.00 (quite like). The nutritional values of cookies product were: 2.29% water content, 3.87% protein, 51.64% fat, 32.55% carbohydrate, 2.38% ashes, 7.27% crude fiber and 622.44 kcal of calorie. Keywords: Cookies, Formulation, Wikao maombo flour.